Od skenograma do digitalnega arhiva - Kragelj, Matjaž (Knjižnica, 2014)
Public institutions hold important physical collections of materials from the fields of culture and science. For more than a decade, they have been facing the problem of digitization and archiving requirements as a part of the digitization process when generating e-content. They are using more or less the same procedures when they cope with those difficulties. At the same time, we note a much larger set of institutions, which still deal, more or less successfully, with the initial problems of the digitization process. The main reasons for the gap between the two can be found among different factors, including: lack of knowledge in the field of the science in informatics, limited financial and staff resources provided by public institutions, and in particular, limited resources for the preservation management and the archive maintenance sub processes. The National and University Library is developing a business model that will provide a successful implementation of the digitization process with all main sub processes (submission and/or digitization, archiving, dissemination). Thus, the end product for long-term preservation and provision of public access to e-content for similar institutions will be ensured. The main component parts of the digitization process are as follows: selection and preparation of physical collections, determination of access/use restrictions or copyright, application of Creative Commons license, preparation of project parameters and bibliographic information, digitization, integration of bibliographic data into e-contents, automatic text recognition, archiving and providing access to digitized collections. Some activities, such as access and longterm preservation, need to be ongoing throughout all the phases of the digitization workflow, whereas some of them can be traced only in individual phases of the process. In special cases, it might be necessary to change some bibliographic data, i.e. license terms and conditions or access modality. The digital copy status can change over time (expiration of licence, the digitized materials fall in the Public Domain) or by modification of agreement with the copyright holder. By implementing a business model, we wish to contribute to the rationalization of the use of public funds for this purpose, but at the same time, to encourage a greater scope of online available e-content and to ensure a safe long-term preservation of e-content material. It should be pointed out that the problems, related to long-term preservation of physical collections and their digital representation are not terminated by the digitization process, they are only expanded from the physical to digital environment.
Keywords: digital archives; digitalni arhivi; digitization; digitalizacija; culture; culture digital collections; kultura; management; digitalne zbirke; upravljanje